Iron Ladies – How Desiccated Asexual Rotifer Adineta vaga Deal With X-Rays and Heavy Ions? - Hespeels, Boris; Penninckx, Sébastien; Cornet, Valérie; Bruneau, Lucie; Bopp, Cécile; Baumlé, Véronique; Redivo, Baptiste; Heuskin, Anne-Catherine; Moeller, Ralf; Fujimori, Akira; Lucas, Stephane; Van Doninck, Karine (Frontiers in Microbiology, 2020)
Space exposure experiments from the last fifteen years have unexpectedly shown that several terrestrial organisms, including some multi-cellular species, are able to survive in open space without protection. The robustness of bdelloid rotifers suggests that these tiny creatures can possibly be added to the still restricted list of animals that can deal with the exposure to harsh condition of space. Bdelloids are one of the smallest animals on Earth. Living all over the world, mostly in semi-terrestrial environments, they appear to be extremely stress tolerant. Their desiccation tolerance at any stage of their life cycle is known to confer tolerance to a variety of stresses including high doses of radiation and freezing. In addition, they constitute a major scandal in evolutionary biology due to the putative absence of sexual reproduction for at least 60 million years. Adineta vaga, with its unique characteristics and a draft genome available, was selected by ESA (European Space Agency) as a model system to study extreme resistance of organisms exposed to space environment. In this manuscript, we documented the resistance of desiccated A. vaga individuals exposed to increasing doses of X-ray, protons and Fe ions. Consequences of exposure to different sources of radiation were investigated in regard to the cellular type including somatic (survival assay) and germinal cells (fertility assay). Then, the capacity of A. vaga individuals to repair DNA DSB induced by different source of radiation was investigated. Bdelloid rotifers represent a promising model in order to investigate damage induced by high or low LET radiation. The possibility of exposure both on hydrated or desiccated specimens may help to decipher contribution of direct and indirect radiation damage on biological processes. Results achieved through this study consolidate our knowledge about the radioresistance of A. vaga and improve our capacity to compare extreme resistance against radiation among living organisms including metazoan.